Technological platforms at the contemporary university - Campos Posada, Raúl; Campos Posada, Gloria Elisa; Boulet Martínez, Ruhadmi (Atenas, 2016)
The conception and the employment of the technological platforms in the contemporary life are broadly extended. In the education and specifically the processes nouns of the contemporary university the technological platforms win in interest for the study, their application and the use of their potentialities. In the article is defined technological platform conceptually, these tools are characterized and it is meditated on the demands that it establishes their use.